2004
DOI: 10.1097/01.nrl.0000138998.11209.88
|View full text |Cite
|
Sign up to set email alerts
|

Anticipating Smallpox and Monkeypox Outbreaks

Abstract: Although the potential neurologic complications of the smallpox vaccine must be weighed against the threat of monkeypox and smallpox, current experience with vaccination suggests it carries a very low risk of neurologic complications and does not lead to exacerbations of chronic neurologic illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Most of the vaccines stockpiled are first-generation vaccines, as were used during the World Health Organization (WHO) smallpox-eradication campaign. Considering the large number of unvaccinated people in present societies, the question arises about how many people would be expected to have serious adverse events, such as postvaccinal encephalitis (PVE [ 1 , 2 ]) or death, after smallpox vaccination. Because PVE had a case-fatality rate of approximately 25%–30%, with 16%–30% of survivors having permanent neurological damage [ 1 , 2 ], the WHO promoted the switch to the Lister strain of vaccinia virus for vaccine production in the 1950s.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the vaccines stockpiled are first-generation vaccines, as were used during the World Health Organization (WHO) smallpox-eradication campaign. Considering the large number of unvaccinated people in present societies, the question arises about how many people would be expected to have serious adverse events, such as postvaccinal encephalitis (PVE [ 1 , 2 ]) or death, after smallpox vaccination. Because PVE had a case-fatality rate of approximately 25%–30%, with 16%–30% of survivors having permanent neurological damage [ 1 , 2 ], the WHO promoted the switch to the Lister strain of vaccinia virus for vaccine production in the 1950s.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the large number of unvaccinated people in present societies, the question arises about how many people would be expected to have serious adverse events, such as postvaccinal encephalitis (PVE [ 1 , 2 ]) or death, after smallpox vaccination. Because PVE had a case-fatality rate of approximately 25%–30%, with 16%–30% of survivors having permanent neurological damage [ 1 , 2 ], the WHO promoted the switch to the Lister strain of vaccinia virus for vaccine production in the 1950s. It has been shown that vaccinia strains differ in their pathogenicity in animals [ 3 ] and that vaccinia strains that are more pathogenic in animals may cause a higher rate of postvaccinal complications in humans after vaccination [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies on the connection between smallpox vaccines and the monkeypox virus. As early as 2004, studies pointed out that vaccination against smallpox affects the manifestation and severity of monkeypox, and it is feasible to treat monkeypox with a subunit vaccine method of smallpox-monkeypox immunization [15,29]. Studies have shown that the smallpox vaccine could achieve an 85% effectiveness rate in preventing monkeypox.…”
Section: Discussionmentioning
confidence: 99%
“…PVEM presents as stupor, coma, seizure, and paraparesis, especially in older children and adults. Around 16% of cases have reported long‐term neurologic effects, while mortality rates amount to 1.5 per million per vaccination recipient (Abrahams & Kaufman, 2004 ). Similar neuropsychiatric complications have been reported for MPX as well (Jezek et al., 1987 ; Sejvar et al., 2004 ).…”
Section: Introductionmentioning
confidence: 99%